Microarray Identifies a Key Carcinogenic Circular RNA 0008594 That Is Related to Non-Small-Cell Lung Cancer Development and Lymph Node Metastasis and Promotes NSCLC Progression by Regulating the miR-760-Mediated PI3K/AKT and MEK/ERK Pathways - Wang, Qiushi; Yan, Chunhua; Zhang, Pengfei; Li, Guanghua; Zhu, Ruidong; Wang, Hanbing; Wu, Libo; Xu, Guangquan (Frontiers in Oncology, 2021)
Purpose: This study aimed to explore the circular RNA (circRNA/circ) profile engaged in non-small cell lung cancer (NSCLC) development and metastasis and to investigate potentially key carcinogenic circRNAs related to NSCLC. Methods: CircRNA profiles between 10 NSCLC tissues and 10 adjacent tissues and between 5 NSCLC tissues with lymph node metastasis (LNM) and 5 NSCLC tissues without LNM were detected by Arraystar Human circRNA Array followed by bioinformatics. Circ_0008594 knockdown, circ_0004293 overexpression and circ_0003832 overexpression plasmids were transfected into H23 and H460 cells to sort potential oncogenic circRNA. Then circ_0008594 overexpression and knockdown plasmids were transfected, followed by that circ_0008594 knockdown plus miR-760 knockdown plasmids were transfected into these cells. Cell proliferation, apoptosis, invasion, stemness and pathways were detected. In addition, xenograft mice models were constructed via injecting H23 cells with circ_0008594 overexpression or knockdown to validate the findings. Results: A total of 455 dysregulated circRNAs in NSCLC tissues versus adjacent tissues and 353 dysregulated circRNAs in NSCLC tissues with LNM versus those without LNM were discovered. Via cross analysis, 19 accordant circRNAs were uncovered, among which three candidate circRNAs (circ_0008594, circ_0004293, circ_0003832) were chosen for functional experiments, during which it was observed that circ_0008549 affected H23 and H460 cell proliferation and apoptosis more obviously than circ_0004293 and circ_0003832. Subsequent experiments showed that circ_0008594 promoted H23 and H460 cell proliferation and invasion but affected stemness less and negatively regulated miR-760 via direct binding. Furthermore, miR-760 attenuated the effect of circ_0008549 on regulating H23 and H460 cell functions and the PI3K/AKT and MEK/ERK pathways. In vivo experiments further confirmed that circ_0008549 increased tumor volume, epithelial-mesenchymal transition, and the PI3K/AKT and MEK/ERK pathways while reducing tumor apoptosis and miR-760 NSCLC xenograft models. Conclusion: Our study identifies several valuable circRNAs related to NSCLC development and LNM. Furthermore, as a key functional circRNA, circ_0008594 was observed to promote NSCLC progression by regulating the miR-760-mediated PI3K/AKT and MEK/ERK pathways.